2012
DOI: 10.1134/s1063785012030066
|View full text |Cite
|
Sign up to set email alerts
|

Receiver protecting device based on microstrip structure with high-temperature superconductor film

Abstract: New design of an effective device for protection against high power electromagnetic pulses has been created based on a pair of noninteracting microstrip resonators, which are coupled in the working fre quency band via a third resonator based on a thin film of high temperature superconductor (HTSC) occur ring in the superconducting state. Under the action of an electromagnetic pulse with the power above a cer tain threshold, the HTSC film element passes from the superconducting to normal (high resistivity) stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…The frequency-dependence of these coefficients originates from individual distribution of voltage and current (as well as magnetic and electric fields) along the resonator's strip at every frequency. Earlier [19], it was shown that, by choosing a resonator shape and a gap between resonators, one can achieve equality between inductive k L and capacitive k C coupling coefficients at some frequency, which means zeroing of total coupling coefficient. When this occurs, a damping pole (a sharp minimum of transmission) results at this frequency.…”
Section: Principle Of Power Limiter Operationmentioning
confidence: 99%
See 2 more Smart Citations
“…The frequency-dependence of these coefficients originates from individual distribution of voltage and current (as well as magnetic and electric fields) along the resonator's strip at every frequency. Earlier [19], it was shown that, by choosing a resonator shape and a gap between resonators, one can achieve equality between inductive k L and capacitive k C coupling coefficients at some frequency, which means zeroing of total coupling coefficient. When this occurs, a damping pole (a sharp minimum of transmission) results at this frequency.…”
Section: Principle Of Power Limiter Operationmentioning
confidence: 99%
“…Previously, [19] has shown that the leakage level in the device depends on the width of the bridge (narrow part) in the HTSC dumbbell-shaped element and it is of the order of tens mW. It is obvious that the critical power (i.e.…”
Section: Principle Of Power Limiter Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in distance S 2 leads to reduction of interaction between outer resonators with each other through inner one, and, as a result, bandwidth decreases. As researches showed earlier [5] for such limiters reduction of bandwidth leads to increasing attenuation of a signal in the limitation mode. That is a positive factor for power limiter.…”
mentioning
confidence: 76%
“…This shortcoming is absent in HTSC power limiters designed on the basis of the new concept [5,6], where limitation occurs due to reflection, not absorption. Such device has a structure of a three-resonator bandpass microstrip filter.…”
mentioning
confidence: 99%